2011
DOI: 10.1159/000327035
|View full text |Cite
|
Sign up to set email alerts
|

The Japanese Aggrenox (Extended-Release Dipyridamole plus Aspirin) Stroke Prevention versus Aspirin Programme (JASAP) Study: A Randomized, Double-Blind, Controlled Trial

Abstract: Background: Despite improvements in treatment, stroke still carries a high death toll and disability in Asia. Extended-release dipyridamole (ER-DP) plus acetylsalicylic acid (ASA) has consistently been shown to be superior over conventional platelet inhibition by ASA. ER-DP plus ASA is well established in the secondary prevention of stroke in a lot of countries including the USA and Europe. DP has an established benefit in the treatment of heart disease in Japan; however, for the prevention of stroke, the fixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 49 publications
1
19
0
1
Order By: Relevance
“…19- 24 The annual incidence of intracranial bleeding during aspirin treatment for secondary prevention of stroke in Japan has been reported as 0.84-1.50%/year, much higher than the 0.13-0.35%/year reported from Western countries. [19][20][21][22][23] Interestingly, no such ethnic differences have been found with clopidogrel treatment for the secondary prevention of stroke. 19, [25][26][27] In an important study, Shen et al identified 18,867 qualifying AF hospitalizations (78.5% white, 8% black, 9.5% Hispanic, 3.9% Asian) and 173 qualifying intracranial bleeding events over 3.3 years of follow-up and found that warfarin was associated with increased intracranial bleeding risk in all races.…”
mentioning
confidence: 99%
“…19- 24 The annual incidence of intracranial bleeding during aspirin treatment for secondary prevention of stroke in Japan has been reported as 0.84-1.50%/year, much higher than the 0.13-0.35%/year reported from Western countries. [19][20][21][22][23] Interestingly, no such ethnic differences have been found with clopidogrel treatment for the secondary prevention of stroke. 19, [25][26][27] In an important study, Shen et al identified 18,867 qualifying AF hospitalizations (78.5% white, 8% black, 9.5% Hispanic, 3.9% Asian) and 173 qualifying intracranial bleeding events over 3.3 years of follow-up and found that warfarin was associated with increased intracranial bleeding risk in all races.…”
mentioning
confidence: 99%
“…This recommendation was supported by four citations [1][2][3][4] , which included a systematic review and meta-analysis; this was used as the starting point for our PubMed search. 4 The meta-analysis focused on seven randomized, controlled studies 1,[5][6][7][8][9][10] ; that included patients with recent history of stroke or transient ischemic attack (TIA); and that compared DPT versus monotherapy. The meta-analysis indicated that DPT was superior to aspirin alone, but not to clopidogrel alone, and that dual anti-platelet therapy was more harmful than clopidogrel.…”
Section: Related Literaturementioning
confidence: 99%
“…Having reviewed relevant clinical trials of patients with a history of ischemic stroke and taking ASA for secondary prevention of ischemic stroke [5,[22][23][24], we applied the transition probabilities for ASA treatment of stroke patients (27.5 per 1000 patient-years for ischemic stroke, 9.7 per 1000 patient-years for hemorrhagic stroke) from the CSPS2 (Cilostazol for Prevention of Secondary Stroke) trial and the transition probabilities for treatment without ASA (57.8 per 1000 patient-years for ischemic stroke, 7.2 per 1000 patient-years for hemorrhagic stroke) from the CSPS (Cilostazol Stroke Prevention Study) [22,23]. Transition probabilities were taken from these two studies because (1) there are no clinical trials directly comparing a placebo arm with an ASA arm; (2) a placebo arm was included only in the CSPS; (3) subjects targeted in the CSPS were similar to those in CSPS2, which also included an ASA arm; and (4) many sites in Japan participated in these trials (183 in CSPS and 278 in CSPS2).…”
Section: Ischemic and Hemorrhagic Strokementioning
confidence: 99%